Malicious/phishing URL detection system in a network with Raspberry Pi (NETBITS) - Mohamad Fauzi, Mohamad Aniq Fakhrul; Abdullah, Lili Marziana (IIUM Press, 2022)
Phishing is an online fraudulent act that has affected many organisations. Organisation and home networks are becoming more susceptible to attacks with the emergence of more and more malicious and phishing URLs, and the increase significance of communication and data storage on the internet. Firewall and antivirus may not be enough against such intrusion. Without a secure and efficient detection system, a local network can easily be penetrated by the attackers or unauthorized individuals. Several existing network intrusion detection products are available out there, but those systems are usually integrated with largescale hardware and difficult for the public to set up, use readily and carry everywhere. This paper reports on a system development project to design and develop a cross-platform malicious/phishing URL detection system, referred to as Netbits. Netbits, built using Django framework based on Python language and installed on Raspberry Pi, can monitor network traffic flow for any malicious activities in real-time. The simulation carried out in a network environment and testing performed showed that Netbits system can detect malicious activities and display the infected scans. Nevertheless, more enhancements may be required before rolling out Netbits to the public.